Particle “by” in Sentences with Conditional Relations - R. Wang (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The cases of the particle by use in sentences containing conditional relations are considered. The relevance of the study is determined, on the one hand, by the current state of study of function words, which provides a comprehensive description of each function unit; on the other hand, by the need for a multi-faceted approach, primarily constructive and semantic, to syntactic phenomena. The novelty of the study is seen, firstly, in the systematization of different manifestations of participation of the particle by in expression of the condition; secondly - in identifying special cases where conditional relations are implicit, in particular at the semantic level. Three main types of participation of particle by for the expression of the condition are revealed: (1) conditional constructions with particle by , (2) constructions with other meanings and implicit manifestation of the condition, (3) non-constructive expression of conditional relations manifested only at the semantic level. In each of three main types there are particular manifestations. In a special constructive expression of condition there are conjunction constructions, in which by becomes a component of conjunction yesli by (constructions with subjunctive mode, infinitive, nominative, etc.), and two non-conjunction conditional constructions with different ratios of modes. Among other constructions with the meaning of alternative motivation (with conjunctions inache , a to , ne to , which can add by ) and adversative construction are mentioned. Special attention is paid to the non-constructive expression of conditional relations contained only in the propositions ratio.